Biomechanical analysis of lumbar spine with interbody fusion surgery and U-shaped lumbar interspinous spacers. Issue 7 (19th May 2021) - Yin, Jia-Yu; Guo, Li-Xin
Abstract: Previous research indicates whole-body vibration may lead to low back pain. The aim of this study is assessing the dynamic characteristics of a lumbar spine with Coflex and Coflex-F (commercial implants used as lumbar interspinous spacers) and effect of lumbar interbody fusion surgery. A transient dynamic analysis is performed on three numerical lumbar spine models under the loading condition of a vertical sinusoidal force of ±40 N with a compressive follower preload of 400 N. Also, Coflex-F model with and without interbody fusion surgery is analyzed under the same loading condition. The results show that the maximum value and vibration amplitude of von Mises stress in annulus ground substance (AGS) and intradiscal pressure (IDP) at implanted segment decrease from healthy model to Coflex model, and Coflex-F model. By contrast, for adjacent segments the maximum value of implanted models are larger than that of healthy model. The maximum value of endplates with and without cage are 2.44 MPa and 1.73 MPa (L4 inferior endplate), 1.94 MPa and 1.42 MPa (L5 superior endplate), respectively. The vibration amplitude of Coflex-F model with fusion surgery is smaller than that without fusion surgery. Coflex and Coflex-F not only protect implanted segment but also have a negative effect on adjacent segments. Inserting cage for Coflex-F model can absorb vibration energy at adjacent segments.